Does Financial Development Affect the Quality of Environment? Evidence From Indonesia - Yollit Permata Sari; Harby Prasetya (Jurnal Ekonomi Pembangunan, 2022)
This study aims to see the effect of financial development on carbon emissions. Using PCA to convert variables into small uncorrelated variables while maintaining the original data, this study uses five variables representing the financial sector converted into two components. The first component consists of variables Domestic credit to the private sector by banks and Domestic credit to the private sector. At the same time, the second component includes variables Domestic credit provided by the financial sector, Market capitalization of listed domestic companies, and Stock Traded. We can conclude from the estimation results that the first component is the banking-based financial sector while the second is the stock-based financial sector. While the results of the study using multiple linear regression to analyze the effect of the financial development on carbon emissions found that the financial bank-based industry had a negative relationship. In contrast, the stock-based financial sector had a significant positive relationship with affecting carbon emissions. There are many ways that the government can do to make the financial sector contribute to environmental safety, such as offering interest discounts to encourage investment in energy-efficient technologies and asking companies to do CSR in projects that are more environmentally friendly